Intraspecific variation in Erica coccinea - Malan, Michelle (Department of Biological Sciences, 2014)
The genus Erica is the most specious in the Cape Floristic Region, with a large range of habitats, pollination syndromes and fire survival strategies. Erica coccinea, like many other Cape Erica species, has high intraspecific variability between populations. In addition to variability in floral characteristics such as colour, this species includes two distinct regeneration forms: a resprouter form which survives fire by resprouting from dormant buds in a swollen lignotuber, and a seeder form which does not survive fire, but whose populations regenerate from fire-triggered seed germination. Previous studies have shown that these two regeneration forms are genetically determined and this dissertation investigates further the differences in floral morphology, phenology, fecundity and genetic relatedness across 29 populations. Results show patterns of seeder individuals investing more effort into nectar and seed production than resprouters and differences in flower colour and flowering phenology between the two fire life history strategies. A PST-FST analysis, comparing genetic variability to variability in floral traits shows a strong selective force working on anther length in the seeder form. A complete separation of flowering phenology between seeder and resprouter individuals in 'mixed' populations where the two forms co-occur leads to speculation that this might be a case of incipient speciation.